BLOOD LIPID PROFILE OF BROILERS FED COMMERCIAL RATIONS SUBSTITUTED WITH PROBIO-BALITANI FERMENTED BAKERY WASTE - J. A. L. S., Malango; Putra, I G. A. A.; Mudita, I. M. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
The study aimed to determine the effect of feeding commercial rations substituted with 1% probiotic fermented bakery waste "Probio-BaliTani" with different levels on broiler blood fat profile. The research was conducted at the Farm of Faculty of Animal Husbandry, Udayana University, Jalan Raya Sesetan, Denpasar. Laboratory analysis was carried out at the Animal Nutrition and Food Laboratory, Jalan P.B. Soedirman and Bali Provincial Health Laboratory Center, Jalan Angsoka, Denpasar. The research was conducted for 35 days. The research design used a completely randomized design (CRD) with 5 treatments and 4 replicates, consisting of commercial rations without substitution of fermented bakery waste probiotics "Probio-BaliTani" (R0), commercial rations substituted with 10% fermented bakery waste 1% probiotics "Probio-BaliTani" (R1), commercial ration substituted with 15% fermented bakery waste 1% probiotic "Probio-BaliTani" (R2), commercial ration substituted with 20% fermented bakery waste 1% probiotic "Probio-BaliTani" (R3), and commercial ration substituted with 25% fermented bakery waste 1% probiotic "Probio-BaliTani" (R4). Each experimental unit consisted of 4 broilers with body weight 51.07 ± 5.53g and unsexed. The observed variables were cholesterol, HDL, LDL, and triglyceride levels. The results showed that the provision of commercial rations substituted with 1% probiotic fermented bakery waste "Probio-BaliTani" level 10-25% (R1, R2, R3, R4) resulted in blood cholesterol, HDL and triglyceride levels that were not significantly different (P>0.05) with R0. Against blood LDL levels, substitution at the level of 10 - 20% (R1, R2, R3) resulted in an increase in blood LDL levels, while the provision of R4 resulted in the same blood LDL levels as the provision of commercial rations without substitution of fermented bakery waste / R0. Based on the results of the study, substitution of commercial rations with 1% probiotic fermented bakery waste "Probio-BaliTani" has not affected cholesterol, HDL and triglycerides, but substitution up to 20% level increases broiler blood LDL levels.